Features of some counting nouns in modern Russian and their national and cultural specificity - Basalaeva, Elena Gennad'evna; Spilman, Marina Vladimirovna (Филология: научные исследования, 2024)
The article examines countable nouns (pyatak, dvushka, etc.), which refer to peripheral means of expressing quantity. In the semantics of such words, the meaning of plurality appears along with a specific subject meaning. There are different approaches to countable nouns (broad and narrow), which entails the problem of the composition of countable nouns, which can be solved by presenting them in the form of a lexical-semantic field. In addition, this vocabulary belongs to the category of nationally specific, which is manifested in its complete or partial non-equivalence in different languages. In the analysis of the material, traditional methods of semasiological study of the word were used: component, definitional, distributional, contextual, discourse analysis, as well as the modeling method. The lexical-semantic field of countable nouns is presented as follows. The core zone includes countable nouns proper, which are lexically and grammatically dependent, in them the idea of ​​quantity is combined with objectivity (ten, dozen, pair). The perinuclear zone contains nouns that name numbers (two, three, ten, etc.). On the periphery are words in which the meaning of quantity is more likely to be guessed, since it is almost completely absorbed by the meaning of objectivity (two, three, etc.). On the deep periphery are nouns with the meaning of "names of persons" (a three-year student, etc.). The article examines the peculiarities of the use of countable nouns in modern Russian. Thus, the sphere of their functioning is mainly colloquial speech (including urban vernacular and partly urban slang). At the same time, a number of countable nouns are used extremely rarely (dozen), while others are used actively and develop new meanings (two). National-specific features of this vocabulary are revealed, due to their partial lack of equivalence.